Rice husk as inexpensive renewable immobilization carrier for biocatalysts employed in the food, cosmetic and polymer sectors - Marco Cespugli; Simone Lotteria; Luciano Navarini; LONZARICH, VALENTINA; Lorenzo Del Terra; Francesca Vita; Marina Zweyer; Giovanna Baldini; Valerio Ferrario; Cynthia Ebert; Lucia Gardossi (Catalysts, 2018)
The high cost and environmental impact of fossil-based organic carriers represent a critical bottleneck to their use in large-scale industrial processes. The present study demonstrates the applicability of rice husk as inexpensive renewable carrier for the immobilization of enzymes applicable sectors where the covalent anchorage of the protein is a pre-requisite for preventing protein contamination while assuring the recyclability. Rice husk was oxidized and then functionalized with a di-amino spacer. The morphological characterization shed light on the properties that affect the functionalization processes. Lipase B from Candida antarctica (CaLB) and two commercial asparaginases were immobilized covalently achieving higher immobilization yield than previously reported. All enzymes were immobilized also on commercial epoxy methacrylic resins and the CaLB immobilized on rice husk demonstrated a higher efficiency in the solvent-free polycondensation of dimethylitaconate. CaLB on rice husk appears particularly suitable for applications in highly viscous processes because of the unusual combination of its low density and remarkable mechanical robustness. In the case of the two asparaginases, the biocatalyst immobilized on rice husk performed in aqueous solution at least as efficiently as the enzyme immobilized on methacrylic resins, although the rice husk loaded a lower amount of protein.